The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/00054725-200411000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA Sequence Analysis of Mucosa-Associated Bacteria in Crohn’s Disease

Abstract: These findings suggest that CD is not caused by invasive pathogens associated specifically with the sites of lesions but that dysbiosis exists in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 20 publications
4
48
0
Order By: Relevance
“…However, conflicting reports do exist where levels of Bacteroides and lactobacilli showed no difference between Crohn's disease samples and control samples, while the bifidobacteria were significantly decreased in numbers (13). Furthermore, culture-independent investigations of the dynamics of the intestinal bacterial community in Crohn's disease have either concentrated on the dominant species (24,44,45,52) or quantified the species in specific groups (53,58), and each analysis has used only a single-timepoint sample with no temporal data presented. The consensus of opinion from these investigations is that there is a reduction in the diversity of the dominant bacterial species in Crohn's disease.…”
mentioning
confidence: 99%
“…However, conflicting reports do exist where levels of Bacteroides and lactobacilli showed no difference between Crohn's disease samples and control samples, while the bifidobacteria were significantly decreased in numbers (13). Furthermore, culture-independent investigations of the dynamics of the intestinal bacterial community in Crohn's disease have either concentrated on the dominant species (24,44,45,52) or quantified the species in specific groups (53,58), and each analysis has used only a single-timepoint sample with no temporal data presented. The consensus of opinion from these investigations is that there is a reduction in the diversity of the dominant bacterial species in Crohn's disease.…”
mentioning
confidence: 99%
“…These studies were also inconsistent in that one group reported an overrepresentation of the phylum Bacteriodetes in Crohn disease and ulcerative colitis tissue, while another group showed no specific bacterial phylum associated with diseased or control tissue. Overall, any reported differences in phylogenetic groups between patients and controls were not sufficiently reproducible to justify the conclusion that organisms of any one group was associated with IBD (43).…”
Section: The Case For the Presence Of Abnormal Microfloramentioning
confidence: 87%
“…Complementary studies using molecular techniques to identify specific bacterial groups have also been applied to the study of the bacterial microflora in IBD (42)(43)(44). These studies do not support the presence of a specific, pathogenic organism in IBD, in that profiles of mucosa-associated bacterial ribosomal DNA showed no difference between inflamed and uninvolved areas.…”
Section: The Case For the Presence Of Abnormal Microfloramentioning
confidence: 99%
“…Indeed, recent studies demonstrate that obesity in humans and ob/ob mice is associated with stereotypical imbalances in the normal gut microbiota (31)(32)(33). Likewise, previous studies of human IBD, using standard culture techniques (34)(35)(36) or molecular analysis (37)(38)(39)(40)(41)(42)(43), have noted alterations in the GI microbiota. However, most of these IBD studies have been limited in statistical power and precision of identification or have examined only the fecal microbiota, which differs substantially from that of the GI mucosa (44).…”
mentioning
confidence: 96%